Wideband 2×2 antenna-in-package based on magneto-electric dipole array antenna for 5G mmWave applications - Yong, Wai Yan; Glazunov, Andrés Alayón (Frontiers in Antennas and Propagation, 2024)
This paper presents an antenna-in-package (AiP) design realised with the conventional multilayer printed circuit board (PCB) manufacturing method. The design consists of a wideband 2 × 2 magneto-electric dipole (MED) array antenna operating from 24.25 -29.5 GHz and a wideband transition from the analogue beamformer integrated into the proposed MED array antenna (IMED).The IMED array antenna has been fabricated with two distinct NXP analogue beamformer chips, i.e., MMW 9004 KC and MMW 9002 KC covering the N257 and the N258 band, respectively. The measured EIRP at P 1dB was 35.3 dBm and 35.1 dBm for the IMED with the MMW 9004 KC and the MMW 9002 KC analogue beamformer chip, respectively. Our proposed antenna demonstrates the feasibility of designing a single wideband AiP that can be integrated with different analogue beamformers operating within the frequency band of the proposed antenna. This is true, provided the RFIC used for integration has the same footprint for RF ports, SPI control ports, and DC power supply ports. The primary benefit of the proposed technique is the design antenna can adapt the operating frequency to different frequency standards by incorporating additional analogue chips without increasing the design complexity. This feature enables the antenna manufacturer to tailor the antenna products to different frequency standardisations depending on where the antenna will be employed. The AiP operates at 5G millimeter-wave (mmWave) frequencies, with the potential for Internet of Things (IoTs) applications. Furthermore, from our simulation results, the proposed IMED can potentially be extended as a phased array antenna with 2D scanning.